Performance of activated carbon from Cassava peel for the removal of Pb (II) in Pb solution / Nur Azzatul Farisya Zurizam, Nor Hafizah Che Ismail and Faiezah Hashim - Zurizam, Nur Azzatul Farisya; Che Ismail, Nor Hafizah; Hashim, Faiezah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study aimed to investigate the potential of cassava peel-activated carbon for the removal of Pb (II) ions from a Pb synthetic solution. Cassava peels are rich in carbohydrates (cellulose and hemicellulose) and lignin, which work well to remove heavy metals. Cassava peel has a high carbon content and a low ash content, and activated carbon may be made from it. Dried cassava peels were carbonised in a muffle furnace at 350°C for one hour and treated with zinc chloride acid (ZnCl2). Activated carbon produced and its physiochemical characteristics, including ash content, iodine number, volatile matter, methylene blue adsorption, moisture content, and pH, were assessed. Results showed that the proximate analysis for the determination of macronutrients of cassava peelings consisted of 77% moisture content, 1% ash content, 2.6 % volatile matter, and 850.43 mg/g iodine number. The result showed that the materials are good precursors for the production of activated carbon and suitable adsorbents for the removal of heavy metals such as Pb (II). The findings of this study will be useful in developing a cost-effective and efficient alternative to activated carbon.